Research on the deposition law of the spray droplet group based on single droplet multiphase flow simulation - Chen, Chongchong; Li, Shougen; Wu, Xiaoyi; Li, Jiale; Jia, Yalan; Kang, Feng; Wang, Yaxiong (Journal of cleaner production, 2023)
In recent years, there has been a frequent occurrence of large-scale pests and diseases, leading to a dramatic increase in the application of pesticides. This practice presents a significant challenge to both the environment and human health. Citrus and apple trees are the most extensively cultivated fruit trees in China, resulting in a significant amount of pesticide usage annually. In an effort to enhance the utilization efficiency of pesticides and decrease the volume of pesticide application, this article employs citrus and apple branches as target subjects to simulate current application parameters. By comparing the deposition quantity of pesticide per unit leaf area under identical application amounts, we summarize the optimal application parameters for these two fruit tree species. Under the optimal application parameters, the application volume of the pesticide solution experienced a reduction of approximately 30% compared to the average application amount. Simultaneously, this article conducted a single droplet impact simulation, and the simulation results were in line with the deposition test principles of droplet groups. The liquid deposition rate is higher when the leaf inclination angle, droplet velocity, droplet size, and the indirect contact angle between the liquid and the leaf are smaller. This study provides guidance on parameter selection for pesticide application in citrus and apple cultivation, while also serving as a methodological reference for research in other areas of atomizer technology. [Display omitted]